Coaching Tutorial System: use case matter of degree seminar - Rosa María Rodríguez Aguilar; Yedid Erandini Niño Membrillo; Rocío Selene Razo Sánchez (Universidad de Guadalajara, 2021)
Information and communication technologies play an important role in education. Coaching systems promote a new teaching method, based on the digitalization and automation of activities. This study presented the construction of a tutorial coaching system in the academic accompaniment of students of the Bachelor's Degree in International Commerce of the Centro Universitario Nezahualcóyotl, of the Universidad Autónoma del Estado de México. The research was divided into four phases: 1) development of instructional models for the design and selection of didactic materials, 2) system design, 3) system programming and 4) evaluation of the coaching system's functionality. The developed system is a potential tool, since it allows the inclusion of the materials best suited to the needs of the student, considering the different educational modalities, making it an innovative tool, easily accessible and suitable in the current digital era.